Design and Realization of Automatic Packet Reporting System (APRS) for Sending Telemetry Data in Nano Satellite Communication System - Raditiana Patmasari; Inung Wijayanto; R. S. Deanto; Y. P. Gautama; Hurianti Vidyaningtyas (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2018)
To communicate with the ground station, nano satellite requires a communication system that serves in real time to regulate the procedure with ground station. One of the missions of nano satellites is the retrieval of telemetry data from sensors that transmitted using APRS technology (Automatic Packet Reporting System). We designed a prototype to monitor sensor by utilizing the APRS. Real-time sensor data was transmitted to monitor through radio using AX.25 protocol. On the transmitter side, an APRS Tracker integrated with a microprocessor ATMEGA 1284P to modulate the AFSK signal. The existence of this AFSK signal is used to transmit and receive telemetry data using handy talky. We use a computer with AGWPE software to demodulate the AFSK signal and UI-View32 to show the telemetry data. The results showed that the telemetry data can be displayed on the receiver side and acquired in real time. The accuracy of temperature sensor received by the receiver is 92.97%, and humidity sensor is 90.57%. There was a delay of 1 second for the reception of telemetry data directly.